Single copy nuclear gene analysis of polyploidy in wild potatoes (Solanum section Petota) - Cai, D.; Rodríguez, F.; Teng, Y.; Ane, C.; Bonierbale, Merideth W.; Mueller, L.A.; Spooner, D.M. (Springer, 2012)
Recent genomic studies have drastically altered our knowledge of polyploid evolution. Wild potatoes (Solanum section Petota) are a highly diverse and economically important group of about 100 species widely distributed throughout the Americas. Thirty-six percent of the species in section Petota are polyploid or with diploid and polyploid cytotypes. However, the group is poorly understood at the genomic level and the series is ideal to study polyploid evolution. Two separate studies using the nuclear orthologs GBSSI and nitrate reductase confirmed prior hypotheses of polyploid origins in potato and have shown new origins not proposed before. These studies have been limited, however, by the use of few accessions per polyploid species and by low taxonomic resolution, providing clade-specific, but not species-specific origins within clades. The purpose of the present study is to use six nuclear orthologs, within 54 accessions of 11 polyploid species, 34 accessions of 29 diploid species of section Petota representing their putative progenitors, and two outgroups, to see if phenomena typical of other polyploid groups occur within wild potatoes, to include multiple origins, loss of alleles, or gain of new alleles.Our results increase resolution within clades, giving better ideas of diploid progenitors, and show unexpected complexity of allele sharing within clades. While some species have little diversity among accessions and concur with the GBSSI and nitrate reductase results, such as S. agrimonifolium, S. colombianum, S. hjertingii, and S. moscopanum, the results give much better resolution of species-specific progenitors. Seven other species, however, show variant patterns of allele distributions suggesting multiple origins and allele loss. Complex three-genome origins are supported for S. hougasii, and S. schenckii, and one of the ten accessions of S. stoloniferum. A very unexpected shared presence of alleles occurs within one clade of S. verrucosum from Central America, and S. berthaultii from South America in six polyploid species S. demissum, S. hjertingii, S. hougasii, S. iopetalum, S. schenckii, and S. stoloniferum.Our results document considerable genomic complexity of some wild potato polyploids. These can be explained by multiple hybrid origins and allele losses that provide a clear biological explanation for the taxonomic complexity in wild potato polyploids. These results are of theoretical and practical benefit to potato breeders, and add to a growing body of evidence showing considerable complexity in polyploid plants in general.